Skirmishing MDR strain of Candida albicans by effective antifungal CeO2 nanostructures using Aspergillus terreus and Talaromyces purpurogenus. (4th May 2020) - Komal, Rimsha; Uzair, Bushra; Sajjad, Shamaila; Butt, Sajid; Kanwal, Amna; Ahmed, Iftikhar; Riaz, Naveeda; Leghari, Sajjad Ahmed Khan; Abbas, Sehrish
Abstract: Emerging antibiotics resistance fungal infectionsis a major global health problem and new antifungal formulations are direly needed to fight drug resistant Candida albicans strains. This study is aimed to synthesize effective antifungal nanostructures of cerium oxide (CeO2 ) using culture filtrates of two common fungal strains Aspergillus terreus and Talaromyces pupureogenus. The fungal strains used in the synthesis were identified by 18S rRNA gene sequencing and deposited to NCBI GenBank with the accession number of MN099077 and MN121629, respectively. The biofabricated CeO2 NPs were characterized by X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR) and Scanning Electron Microscopy (SEM). Pure CeO2 nanoparticles (NPs) synthesized using Aspergillus terreus culture filtrate were depicted spherical morphology with average size of 28.5 nm. The CeO2 NPs synthesized using Talaromyces pupureogenus revealed the presence of nanosponges with average size of 21.4 nm. Gas chromatography mass spectrometry of culture filtrates of respective strains indicated the presence of ethanol, 1-propanol and tri-chloromethane in culture filtrate of Aspergillus terreus and with addition of palmitic acid in Talaromyces pupureogenus culture filtrate which may have a function as bio reducers and capping agents. Dose dependent anticandidal activity of CeO2 NPs using various different concentrations (100, 200, 300, 600 μ g ml −1 ) synthesized by both fungal strains was observed by disc diffusion assay against Candida albicans as evidenced by increase in size of zone of inhibitions with increasing concentration of CeO2 NPs. Further in-vitro and in-vivo experiments are required to access the potential of CeO2 NPs for controlling Candida albicans strains.